Risk Factors of Hyponatremia in Children with Lower Respiratory Tract Infection (LRTI) - Chinmaya Mahapatra; Vinod Kumar Sharma; Siddhant Singhal; Roshan Kumar Jangid; Tagaram Karthik Laxminath (Journal of Pediatric Research)

(untitled)
Aim:Lower respiratory tract infection (LRTI) is a serious illness especially in children under 5 years of age. Hyponatremia is the most common electrolyte abnormality seen in hospitalized children. This study aimed to evaluate the correlation between hyponatremia in children admitted to a paediatric ward, in the setting of acute LRTI in different age groups and to determine the association of hyponatremia with different types of acute LRTI in children.Materials and Methods:This study included 231 clinically diagnosed children (1 month to 12 years) with acute LRTI. General examinations and systemic examinations were performed. Laboratory investigations included serum electrolyte level (Na+) and radiological investigations included chest X-ray. The conditions observed in the children included bronchopneumonia (BPN), lobar pneumonia, wheeze-associated LRTI (WALRI), bronchiolitis, and empyema. Statistical analysis was carried out using SPSS 16.0 version. A p-value <0.05 was considered statistically significant.Results:Out of 231 cases, hyponatremia was present in 136 cases (58.9%). Mild, moderate, and severe hyponatremia were present in 83.8%, 13.2%, and 2.9% patients, respectively. Most of the patients with BPN had mild hyponatremia (89%). The prevalence of hyponatremia was significantly higher in children aged 6-10 years [odds ratio (OD)=4.29, 95% confidence interval (CI)=0.90-20.45, p<0.05], females (OR=0.56, 95% CI=0.32-0.96, p=0.03) and cases of empyema (OR=4.49, 95% CI=1.48-13.60, p=0.008).Conclusion:In conclusion, among children hospitalized with LRTI, an older age (6-10 years), being female, and the presence of empyema are significant risk factors for the development of hyponatremia. In such children, serum electrolytes should be regularly measured to prevent adverse clinical outcomes.